Characterization of Biochar Produced From Oil Palm Fronds Using The Pyrolysis Method - Dana Restu Farista; Siti Aisyah (Vokatek: Jurnal Pengabdian Masyarakat, 2026)
Oil palm fronds are one of the solid wastes generated in large quantities from oil palm plantation activities. The increasing area of oil palm plantations has led to a higher production of biomass waste, including oil palm fronds, which are still not utilized optimally. One alternative utilization is converting oil palm fronds into biochar through the pyrolysis process. This study aims to characterize biochar produced from oil palm fronds using a retort pyrolysis method and determine its elemental composition through CHNS/O analysis. The research was conducted using a retort pyrolysis method at temperatures ranging from 350°C to 400°C. The resulting biochar was analyzed using a CHNS/O Elemental Analyzer to determine the contents of carbon (C), hydrogen (H), oxygen (O), nitrogen (N), and sulfur (S). The data obtained were analyzed descriptively to characterize the elemental composition of the produced biochar. The CHNS/O analysis showed that the biochar contained 71.85% carbon, 3.75% hydrogen, 21.93% oxygen, 1.68% nitrogen, and 0.33% sulfur. The results indicate that oil palm fronds can be effectively converted into carbon-rich biochar through the retort pyrolysis method. This biochar has potential applications in sustainable biomass management, soil improvement, and environmental remediation.